Vasoactive peptides in the heart of Champsocephalus gunnari - MASINI, MARIA ANGELA; M. Sturla; B. M. Uva (Comparative Biochemistry and Physiology Part A: Physiology, 1997)
The presence of vasoactive peptides known to control cardiovascular functions in mammals and sub-mammalian vertebrates was investigated in the sub-Antarctic icefish Champsocephalus gunnari. Western immuno blotting was used to demonstrate immunoreactive atrial natriuretic peptide (ANP), angiotensin II (Ang II), bradykinin (BK) and endothelin-1 (ET-1) in heart homogenates. Immunohistochemistry was used to investigate the distribution of ANP, Ang II, BK and ET-1 in the cardiocytes of the three chambers of the heart (atrium, ventricle and the very short conus arteriosus).